1999
DOI: 10.1093/jnci/91.9.779
|View full text |Cite
|
Sign up to set email alerts
|

Cancer, Heart Disease, and Diabetes in Workers Exposed to 2,3,7,8-Tetrachlorodibenzo-p-dioxin

Abstract: Our analyses suggest that high TCDD exposure results in an excess of all cancers combined, without any marked specificity. However, excess cancer was limited to the highest exposed workers, with exposures that were likely to have been 100-1000 times higher than those experienced by the general population and similar to the TCDD levels used in animal studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
248
2
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(263 citation statements)
references
References 15 publications
11
248
2
1
Order By: Relevance
“…These findings are consistent with other studies of TCP and PCP workers (Ott et al, 1993;Schecter et al, 1996;Heederik et al, 1998;Coenraads et al, 1999;Ryan and Schecter, 2000). As mentioned earlier, the chlorophenol workers from the Midland plant have been included in the NIOSH Dioxin Registry (Steenland et al, 1999;Piacitelli et al, 2000). Recent analyses of this Registry have omitted workers with PCP and TCP exposure to ''avoid possible confounding of 2,3,7,8-TCDD effects with PCP'' (Steenland et al, 1999).…”
Section: Congeners In Pptsupporting
confidence: 80%
See 2 more Smart Citations
“…These findings are consistent with other studies of TCP and PCP workers (Ott et al, 1993;Schecter et al, 1996;Heederik et al, 1998;Coenraads et al, 1999;Ryan and Schecter, 2000). As mentioned earlier, the chlorophenol workers from the Midland plant have been included in the NIOSH Dioxin Registry (Steenland et al, 1999;Piacitelli et al, 2000). Recent analyses of this Registry have omitted workers with PCP and TCP exposure to ''avoid possible confounding of 2,3,7,8-TCDD effects with PCP'' (Steenland et al, 1999).…”
Section: Congeners In Pptsupporting
confidence: 80%
“…As mentioned earlier, the chlorophenol workers from the Midland plant have been included in the NIOSH Dioxin Registry (Steenland et al, 1999;Piacitelli et al, 2000). Recent analyses of this Registry have omitted workers with PCP and TCP exposure to ''avoid possible confounding of 2,3,7,8-TCDD effects with PCP'' (Steenland et al, 1999). Our evaluation of serum dioxin levels in this study indicated that PCP and TCP workers have similar TEQs based on congener potencies to 2,3,7,8-TCDD.…”
Section: Congeners In Pptmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports based on mortality rates analysis [6,7] or on self-reported diabetes also show associations between environmental pollution levels and prediabetes and/or diabetes [8][9][10]. However, in only few studies was diabetes diagnosed with the aid of fasting plasma glucose (FPG) (≥126 mg/dl [7.0 mmol/l]), HbA 1c (>6.1%) [9] or random glucose level (≥200 mg/dl=11.1 mmol/l) [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to dioxins has recently been associated with an increased risk of diabetes [1]. Prospective cohort studies of individuals exposed to 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), the most potent dioxin congener of persistent organic pollutants (POPs) in occupational or accidental settings, have reported increased risk of diabetes, modified glucose metabolism or insulin resistance [2][3][4][5][6]. Type 2 diabetes was associated with the exposure to dioxin-containing Agent Orange in Vietnam [7].…”
mentioning
confidence: 99%